Strategi Pembelajaran Bahasa Arab Berbasis Aktivitas dalam Penguasaan Mufradät Kelas VII MTsN I Yogyakarta Tahun Ajaran 2017/2018 - Najihah, Fikriatun; Vika Faiza Rahma (Mahira: Journal of Arabic Studies & Teaching, 2023)
This study aims to determine the implementation process as well as the advantages and disadvantages of activity-based Arabic learning strategies in mastering mufradāt in class VII MTsN 1 Yogyakarta. This research is a field research conducted at MTsN 1 Yogyakarta with data collection methods through observation, interviews, and documentation. Data analysis used data reduction, data presentation, and conclusion drawing techniques, and data validation was carried out through triangulation of sources and methods. The results showed that the implementation process of this strategy consisted of planning and implementation stages, which included introduction, core activities, and closing. Core activities include listening and imitating, rereading vocabulary, and singing together. The advantages of this strategy are the balance between students' physical, mental, emotional, and intellectual activities, learning becomes more fun, interactive, and effective, and makes it easier for students to understand the material. This strategy also changes the negative view of Arabic lessons. However, the disadvantages include limited learning media, school facilities that are not yet optimal, the absence of an Arabic language laboratory, an Arabic-speaking environment that has not been formed, and some students who are still passive and shy to participate.